Detection of saliva morphine using surface‐enhanced Raman spectroscopy combined with immunochromatographic assay. (17th January 2020) - Li, Wei; Li, Xiaozhou; Yang, Tianyue; Guo, Xingjia; Song, Youtao
Abstract: An immunochromatographic assay (ICA) based on surface‐enhanced Raman scattering (SERS) method was developed for the detection of morphine in this study. Indirect competitive immunoadsorption was adopted in the ICA due to the small molecular weight of morphine. Antibody modified gold nanoparticles in the ICA were labeled with Raman reporters and were used as the SERS enhancement substrate. By measuring the feature peaks of Raman reporter MBA at 1, 078 cm −1, a quantitative estimation of morphine can be obtained. The limit of detection of this ICA‐SERS method was 2.4 × 10 −4 ng/ml for morphine, which was four orders of magnitude lower than the visual method. This study demonstrated that the proposed ICA‐SERS method is a good candidate for the rapid and accurate detection of illicit drugs in saliva. All the analyses in this paper were carried out in a Microsoft (MS) Excel platform using embedded R functions through Excel BERT add‐in. Abstract : An immunochromatographic assay (ICA) based on surface‐enhanced Raman scattering (SERS) method was developed for the detection of morphine in saliva. An indirect competitive immunoadsorption mechanism was utilized due to the small molecular weight of morphine. By monitoring the feature peaks of Raman reporter MBA at 1, 078 cm −1, a quantitative estimation of target morphine can be obtained.